PENINGKATAN KEMAMPUAN MATEMATIKA ANAK MELALUI PERMAINAN DADU ANGKA GAMBAR RUMAH JAMUR TAMAN KANAK-KANAK AL-AZHAR BUKITTINGGI - Fitrita, Fitrita (Universitas Negeri Padang, 2012)
The background research is that the ability of children to know the numbers are still low. This is caused by the activities on the board and explained the child was asked to write in the book. The purpose of this study to improve the mathematical skills of children through the game of dice numbers with drawings held in mushroom houses Kindergarten Bukittinggi Islam Al-Azhar. In Cycle I rose well but in the second cycle better this suggests that the number of dice game with a picture of the mushroom can improve math skills of children.